Effects of dietary approaches to prevent hypertension and enhance cardiovascular health - Arumugam Vignesh; Thomas Cheeran Amal; Aravindan Shanmugam; Krishnan Vasanth; Subramaniam Selvakumar (Discover Food)
Abstract Hypertension (HT) significantly impacts cardiovascular health (CVH) by exerting chronic stress on arteries and the heart, leading to severe health complications. This review explores the intricate relationship between dietary choices and high blood pressure (BP). Dietary choices are crucial in both the development and management of high BP. Excessive sodium intake is a well-documented risk factor for HT, and strategies to reduce salt consumption can mitigate its adverse effects. Processed and packaged foods also pose severe risks due to hidden sodium and other unhealthy ingredients, making healthier alternatives essential. Potassium plays a vital role in managing BP, with potassium-rich foods supporting a balanced diet. Saturated and trans fats contribute to elevated BP, and healthier fat alternatives are recommended. Excessive sugar consumption negatively affects BP, with hidden sugars in popular foods requiring practical strategies for reduction. Alcohol and caffeine also influence BP, and moderate consumption is advised to avoid potential risks. The Mediterranean diet offers a holistic, evidence-based approach to enhancing CVH, with practical advice and meal plans for a flavourful and health-promoting dietary regimen. Graphical abstract